Root hydraulic phenotypes impacting water uptake in drying soils - Cai, Gaochao; Ahmed, Mutez A.; Abdalla, Mohanned; Carminati, Andrea (Plant, cell and environment, 2022)
Soil drying is a limiting factor for crop production worldwide. Yet, it is not clear how soil drying impacts water uptake across different soils, species, and root phenotypes. Here we ask (1) what root phenotypes improve the water use from drying soils? and (2) what root hydraulic properties impact water flow across the soil–plant continuum? The main objective is to propose a hydraulic framework to investigate the interplay between soil and root hydraulic properties on water uptake. We collected highly resolved data on transpiration, leaf and soil water potential across 11 crops and 10 contrasting soil textures. In drying soils, the drop in water potential at the soil–root interface resulted in a rapid decrease in soil hydraulic conductance, especially at higher transpiration rates. The analysis reveals that water uptake was limited by soil within a wide range of soil water potential (−6 to −1000 kPa), depending on both soil textures and root hydraulic phenotypes. We propose that a root phenotype with low root hydraulic conductance, long roots and/or long and dense root hairs postpones soil limitation in drying soils. The consequence of these root phenotypes on crop water use is discussed. Summary statement During soil drying, the drop in soil–plant hydraulic conductance causes a decline in root water uptake, which is impacted by soil and root hydraulic phenotypes. Lower root conductance, longer root length and longer root hairs would allow plants to maintain water uptake at lower soil matric potential.